PROPUESTA DE UN PROGRAMA DE INTERVENCIÓN PARA LA CREACIÓN DE UNA ASOCIACIÓN DE MINEROS ARTESANALES, DESDE EL ENFOQUE DEL AUTODESARROLLO COMUNITARIO, EN LA COMUNIDAD DE NAMBIJA - Muñoz Vizhñay, Jorge Patricio (2016)
The purpose that has borne to the realization of this thesis is, the one of opting from the focus of the community autodesarrollo, to be able to start the practice of character autosustentable, when carrying out a community intervention with the miners of the area of Nambija located in the parish of San Carlos of the Mines, belonging to the canton Zamora of Zamora's county Chinchipe; as primordial point the activity is framed, to guide the handmade mining population of Nambija to that it executes this mining practice framed in what indicates the law with responsibility and in harmony with the nature. Once executed the present scientific investigation of thesis of Master, is indicated that it corresponds to a community reality of local character, in the one that a hypothetical action has been developed, formulated technically on the realization of the investigation, the idea that it can conform to an association of handmade miners in the population of Nambija, with the one that will be able to put into practice immediate actions in favor of the health, economy, education and in short better days for the population that inhabits the area. Being the present problem, of current character and in a level of local concern and of national expectation for the Ecuadorian state, for the high risk that represents the execution of illegal mining, the present study echo it has been made of that, it stops once presented the problem, inside the investigation to give solution approaches to the established problem. The present investigation indicates that, The National government, for the sake of solving the problem of illegal mining, it has been forced to evict the illegal 11 handmade miners, in this case of Zamora Chinchipe, turning out to be in great majority the evicted miners belonging to the sector of Nambija. In the development of the investigation we have taken into account that these actions have not solved the problem of illegal mining, on the contrary it has caused other inconveniences as they are: unemployment, delinquency, new habits of life contrary to the development apart from that you/they continue carrying out this mining practice of subsistence in far away places where it is not affordable for the authorities and that it bears to that exist more risks for people than they practice these activities. This community reality, you restitution in a challenge for the community inspector, since the present investigation seeks to be a contribution from a vision micro of solution of the illegal mining problem, with perspective of ending up being a solution macro, this proposal is presented at the moment from the local thing and to be used with considerations to be able to solve a problem of national character. The presented topic, he/she has direct relationship with the Community Development, matter in question of scientific study in this Master; for that which we have taken into account for the improvement of the present thesis the problem observed in the population of handmade miners of the sector of Nambija: Going to the same problem that the handmade miners of the area of Nambija confront, we will write down the following ones: Prevention of risks doesn't exist, to the moment to execute the mining activity; They don't use production 12 technology, they apply you practice totally rustic; They don't possess training in the areas: mining, educational, of environmental reparation, of health, environmental, prevention of risks; They don't have a wide neither significant economic interest, more than one of daily expense; The State has problems for the regularization of the miners of the area of Nambija and of Zamora Chinchipe; They lack to implant political of government that favor to the sector of the handmade mining; The handmade and rustic mining works, demand the use of chemical of high danger, the same ones that are poured in the water of rivers, gulches and rills, contaminating those slopes, waters down; likewise they use and they burn chemical, as the mercury, main material used to purify the gold with what you/they alter the intervened ecosystems, the atmosphere and directly the air that is breathed; The community of miners of the neighborhood Nambija of the parish Cumbaratza of the canton Zamora belonging to Zamora's county Chinchipe, is not legalized and they work in a rustic way, what alters the atmosphere of the ecosystem of the Place and of the areas of the low part; The present problem turns out to be a topic of political character - Economic - Social - environmental, of local and national extension, to more than that it is left suitable that the present intention of community organization, will bear to the training of the community of handmade miners in different areas, what means instruction for this community using professionals in the different areas to instruct: mining, environmental, economic, social, legal, I develop productive, accounting, health, organizational and of more elements to work in the topic. Of the data that one scores in the present community intervention carried out to the area of Nambija, he/she intends as solution hypothesis to their common 13 problems, carrying out a community intervention to the community of handmade miners of Nambija, with the purpose of they are able to become unified around a legal organization, for what the scientific problem was assumed to solve with the present investigation, making the interrogation: HOW TO CONTRIBUTE TO THE CREATION OF AN ASSOCIATION OF HANDMADE MINERS, IN THE COMMUNITY DE NAMBIJA, FROM THE FOCUS OF THE COMMUNITY AUTODESARROLLO? It was established as general objective of this scientific study: "Proposing an intervention program for the creation of the Association of Handmade Miners of the Community of Nambija, starting from the principle of the community autodesarrollo." The specific objectives taken into account and carried out in the present investigation they were developed in the following way: to. - it has been based the importance of the principle of the community autodesarrollo theoretically for the asociatividad of handmade miners, making emphasis in the critical points related to the modus vivendi of the reality of this community of miners in their habitat, correlating it included with other communities of different national and international sectors, of what is glimpsed that the disorganization causes a series of activities antiecológicas, destructive pollutants, degrading, of the ecosystems and of its own lives; In the course of the investigation the effectiveness of the principle of the community autodesarrollo is demonstrated allowing the community inspector in a tactical 14 way to introduce and hurried in the problem of the community, in this case of the handmade miners. b. - You proceeded with the realization of an I diagnose fundamental and I practice on the current state that the community of handmade miners of the sector of Nambija lives, what gave a coincident conclusion as a result from different conflicting points, such as socioeconomic, of health, atmosphere, of territorialidad, of housing, legal mark, infractions, among other many more; declared the reality vivenciada, one worked in discovering the conditions that exist for the creation of the association of handmade miners of the community of Nambija, being observed that the desperation of the community, when feeling that cannot develop its economic activity of sustenance in a legal normative way, exists the indicative one that the conditions are very wide and favorable to achieve that objective. c. - Already immerses in the construction of a possible solution to the investigated problem, one worked the elaboration of the proposal of the program of community intervention that facilitates the creation of the handmade mining association in the community of Nambija. For them one worked inside the meetings grupales offering an interaction of cognitive feedback in related different aspects to increase knowledge on the realities and solutions to the problematic vivencial, being was given this way chats pointing to the health, environmental protection, housing, economic entrance, family, territory, technical mining, organization, among other more, culminating with information of legal character to constitute an Artificial Association of handmade miners and 15 information to be mining handmade inscribed legally in the face of the competent authority. In the development of the investigation, the Methodology of the Community Autodesarrollo was applied as high-priority alternative of community intervention. The Dialectical Historical method was applied to this investigative study: with different methodological edges in second plane, what I offer approach vivencial, correlation and exchange of ideas, between the accionantes community inspector and the fellow plaintiff of the action community inspector; Feeding possibility to the database inspector; invigoration of constructive assertive and critical actions, of efficiency and effectiveness to the moment to develop satisfactory results of taking of decisions comunitariamente speaking. This investigation allowed to know data on the family educational formation, housing, reparation environmental expectations of life, social situation, I work remunerated, I develop family productive partner, invigoration and premeditation of community development, among other more data that happen in the day-to-dayness of the community of handmade miners of Nambija. In the same development of the investigation, it demonstrates us that it is of a lot of importance the one that is possible to carry out an association of handmade miners urgently, in the community of Nambija, this with the purpose, of to organize them and to qualify them in what means a mining exploitation in harmony with the nature, friendly and tecnificada, the same one that will achieve an environmental impact of little magnitude. 16 When putting into practice the recommended execution of this study, as it is it the one that is possible to organize to the handmade mining community of the sector of Nambija, in an Artificial Association, the investigation indicates that one will be able to avizorar and to establish economic achievements shared among the handmade miners that conform it to more than that will take advantage all the invested resources in a rational and sustainable way, what meant a saving when taking place and with it better economic revenues, adding the one that will be avoided catastrophic risks and illnesses. We would be being able to avoid carrying out, practical antiecológicas; an excellent increment of the asociatividad of development productive miner in harmony with the nature; the sustainable community interaction would be increased, being able to focus the realization of reparation projects, housing, control of risks, education, health, etc. It was possible to focus the proposed present of intervention, leaving initiate completely and to a step of being able to establish this organization of legal character, action subject to an organizational continuity of leaderships that you/they take them to carry out the administrative administration so that they conform to like an Association of handmade miners, for that which you/they can even request help to different state offices of character juridical legal technician, so that they activate this achieved objective of having been unified and to be able to be organized legally to later. For then to be able to request the corresponding permits on the part of the mining authority and with it one would work, in the productive part strengthening the economic approach with credits through the National Financial Corporation (CFN) and the National Bank of 17 Development (BNF), of the private and included banking, putting into practice the asociatividad techniques, it would not be distant of forming a saving cooperative and credit in the sector, what means more profitability for the organized handmade miners.